2019
DOI: 10.1002/qute.201900023
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Prediction for Large Organic Crystal Structures with Machine Learning

Abstract: Machine‐learning models are capable of capturing the structure–property relationship from a dataset of computationally demanding ab initio calculations. Over the past two years, the Organic Materials Database (OMDB) has hosted a growing number of calculated electronic properties of previously synthesized organic crystal structures. The complexity of the organic crystals contained within the OMDB, which have on average 82 atoms per unit cell, makes this database a challenging platform for machine learning appli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 68 publications
4
48
1
Order By: Relevance
“…As a point of reference, a trivial model that simply predicts the mean band gap for every MOF would have an MAE of 0.97 eV, suggesting that CGCNN captures much of the underlying chemistry. The 44,68,126,127 It is also worth noting that the experimentally measured band gaps of MOFs can vary by several tenths of an electronvolt depending on the synthesis and post-treatment conditions. 128 As such, an MAE less than 0.3 eV is promising for the identification of structure-property trends and for sorting material candidates by band gap, the latter of which is further justified by the CGCNN's high Spearman rank-order correlation coefficient of r = 0.93.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…As a point of reference, a trivial model that simply predicts the mean band gap for every MOF would have an MAE of 0.97 eV, suggesting that CGCNN captures much of the underlying chemistry. The 44,68,126,127 It is also worth noting that the experimentally measured band gaps of MOFs can vary by several tenths of an electronvolt depending on the synthesis and post-treatment conditions. 128 As such, an MAE less than 0.3 eV is promising for the identification of structure-property trends and for sorting material candidates by band gap, the latter of which is further justified by the CGCNN's high Spearman rank-order correlation coefficient of r = 0.93.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…With the database grown to a decent size we furthermore see great opportunities in training machine learning models. We have recently shown that such machine learning tools can be applied to predict basic materials properties for extremely complex organic materials hosting thousands of atoms in the unit cell and with that are outside the realm of materials which can be calculated straightforwardly using density functional theory [36]. In a similar manner, we Figure 5.…”
Section: Discussionmentioning
confidence: 95%
“…The vast increase of experimental and theoretical data obtained over the past century has opened a novel approach to materials research based on computer science methods and the construction of materials databases [18][19][20][21][22][23][24][25]. Such databases were successfully applied in mining for functional materials [21,[26][27][28][29][30][31][32] and as training * hellsvik@kth.se data for machine learning algorithms predicting complex materials properties [33][34][35][36], bypassing computationally demanding ab initio calculations. In this article we report about the implementation of a novel dataset for organic magnets into the organic materials database OMDB [19,37], available at https://omdb.mathub.io.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of the novel materials and structures are obtained mainly due to the capability of AI models in finding the good balance between rationale microstructures and high accuracy, such that to effectively satisfy the performance requirements for those architected materials and structures [286][287][288][289]. Comparing with the applications in other fields, AI has not debuted in materials and structures until recent years [290][291][292][293][294][295][296][297][298][299][300]. Studies have been reported on using AI algorithms to emulate complex biological processes (e.g.…”
Section: Ai and Its Applications In Architected Materials And Structuresmentioning
confidence: 99%